In vitro study of parasite elimination and endothelial protection by curcumin - Kunwittaya, Sarun; Treeratanapiboon, Lertyot; Srisarin, Apapan; Isarankura-Na-Ayudhya, Chartchalerm; Prachayasittikul, Virapong (Technische Universität Dortmund, 2014)
Plasmodium falciparum infection can abruptly progress to severe malaria and cerebral malaria. Despite the current efficiency of antimalarial drugs in killing parasites, no specific effective treatment has been found for cerebral malaria. Thus, a new strategy targeting both parasite elimination and endothelial cell protection is urgently needed in this field. In this study, we determined whether curcumin, which has blood-brain permeability, antioxidative activity and/or immunomodulation property, provided a potential effect on both parasite elimination and endothelial protection. Murine brain microvascular endothelial cells (bEnd.3; ATCC) were cocultured with Plasmodium falciparum-infected red blood cells (Pf-IRBC), peripheral blood mononuclear cell (PBMC) and platelets. Apoptosis of endothelial cells was demonstrated by annexin V staining. Interestingly, curcumin exhibited high efficiency of antimalarial activity (IC50~10μM) and decreased bEnd.3 apoptosis down to 60.0% and 79.6% upon pre-treatment and co-treatment, respectively, with Pf-IRBC, platelets and PBMC. Our findings open up a high feasibility of applying curcumin as a potential adjunctive compound for cerebral malaria treatment in the future.
adjunctive therapy for cerebral malaria
EXCLI Journal ; Vol. 13, 2014
Keywords: apoptosis; brain endothelial cells; curcumin; malaria; Plasmodium falciparum; 610